Exploring avoidance coping among first-year medical students: A qualitative study - Ratna Gumilang Sari; Sri Maria Puji Lestari; Mardheni Wulandari; Stri Nareswari (JOURNAL OF Mental Health Concerns, 2026)
Background: First-year students of the Medical Education Program at the Faculty of Medicine, Universitas Malahayati experience substantial academic pressure from the beginning of their studies. These challenges may generate significant stress and encourage students to adopt avoidance coping strategies as a way of managing academic demands and adaptation difficulties. Purpose: To explore avoidance coping behaviours among first-year students of the Medical Education Program. Method: A qualitative phenomenological design was employed. Data were collected through Focus Group Discussions (FGDs). Participants were selected using purposive sampling to obtain diverse perspectives based on gender, academic achievement (high, moderate, and low block scores), age, and residential status (living in dormitories and non-dormitories). Data were analysed using thematic analysis to identify patterns and themes related to avoidance coping behaviours among first-year medical students. Results: The findings revealed that avoidance coping behaviours among first-year medical students were manifested through several strategies, including escape coping, distraction coping, behavioural avoidance, and emotion-focused coping. The most frequently reported strategies were distraction coping and behavioural avoidance, including excessive social media use, sleeping, engaging in recreational activities, and postponing academic responsibilities. These behaviours were influenced by internal factors, such as emotional responses and self-regulation abilities, as well as external factors, including academic demands and environmental pressures. Conclusion: Avoidance coping behaviours among first-year medical students emerged as responses to academic demands and adaptation challenges within the medical education environment. Understanding these coping patterns may support the development of appropriate psychological support strategies for students during the early stages of medical education. Keywords: Avoidance Coping; Exploration; First-Year Students; Medical Students.